Synthetic nonamer peptides derived from insect defensin mediate the killing of African trypanosomes in axenic culture - Kitani, H.; Naessens, Jan; Kubo, M.; Nakamura, Y.; Iraqi, F.A.; Gibson, John P.; Yamakawa, M. (Springer, 2009)
Synthetic antimicrobial 9-mer peptides (designated as peptides A and B) designed on the basis of insect defensins and their effects on the growth of African trypanosomes were examined using two isolates of Trypanosoma congolense, IL1180 and IL3338, and two isolates of Trypanosoma brucei brucei, ILTat1.1and GUTat 3.1, under axenic culture conditions. Both peptides inhibited the growth of all bloodstream form (BSF) trypanosomes at 200–400 μg/mL in the complete growth medium, with peptide A being more potent than peptide B. In addition, these peptides exhibited efficient killing at 5–20 μg/mL on BSF trypanosomes suspended in phosphate-buffered saline, whereas procyclic insect forms in the same medium were more refractory to the killing. Electron microscopy revealed that the peptides induced severe defects in the cell membrane integrity of the parasites. The insect defensin-based peptides up to either 200 or 400 μg/mL showed no cell killing or growth inhibition on NIH3T3 murine fibroblasts. The results suggest that the design of suitable synthetic insect defensin-based 9-mer peptides might provide potential novel trypanocidal drugs.